Prediction of first marriage age in China and factors associated with marriage delay: Analysis of the 2020 national census data - Qihang Zhao; Dongxia Zhao (PLoS ONE, 2025)
China is undergoing the second demographic transition. This paper constructs provincial-level Net nuptiality tables by gender and urban-rural residence using national census data. We compare spatial patterns of expected years in the single state among Chinese subpopulations and analyze determinants of marriage delay. Results indicate a consistent postponement of first marriage. In 2020, the expected duration of singlehood since birth reached 33.63 years for males and 29.56 years for females. Urban males and rural females exhibited tendencies toward earlier marriage. Key determinants delaying first marriage included educational attainment and the proportion of ethnic minorities, which exerted antagonistic effects. The postponement effect of education outweighed the inhibitory influence of ethnic cultural factors, collectively driving the sustained rise in China’s age at first marriage.